The effect of dragon fruit juice and ambon banana juice on hemoglobin (hb) levels in adolescent girls - Yuli Yuliana; Maryan Syarah; Rita Ayu Yolandia; Kiki Rizkiah; Yuni Nur Amelia; Wati Wati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: One of the non-pharmacological effort to increase hemoglobin (Hb) levels is by consuming fruits that contain iron and nutrients that support red blood cell formation. Dragon fruit contains iron, vitamin C, and antioxidants, while Ambon bananas contain iron, vitamin B6, vitamin C, and folic acid. Purpose: to determine the effect of dragon fruit juice and Ambon banana juice on hemoglobin levels among adolescent girls. Method: The research method used was a descriptive case study involving four respondents, consisting of two respondents in the dragon fruit juice group and two respondents in the Ambon banana juice group, conducted over 14 days. Hemoglobin levels were measured before and after the intervention. Results: The results showed that the dragon fruit juice group experienced an average increase in Hb levels of 1.95 g/dL, while the Ambon banana juice group experienced an average increase of 1.4 g/dL. Conclusion: both dragon fruit juice and Ambon banana juice had an effect on increasing Hb levels in adolescent girls, and dragon fruit juice was more effective than Ambon banana juice in improving Hb levels. Suggestion: Both dragon fruit juice and Ambon banana juice can help improve Hb levels; however, dragon fruit juice is more effective and may be used as an alternative non-pharmacological intervention to help prevent and manage anemia in adolescent girls.